The role of glutathione S-transferases (GSTs) in insecticide resistance in crop pests and disease vectors - Pavlidi, Nena; Vontas, John; Van Leeuwen, Thomas (Current opinion in insect science, 2018)
•GSTs confer resistance by metabolizing or sequestering insecticides or by protecting against oxidative stress caused by insecticides.•The role of BdGSTe2, BdGSTe4 and AfGSTe2 in resistance has recently been validated by RNAi.•TuGSTd05, BmGSTu2 and AfGSTe2 have recently been shown to metabolize insecticides in vitro. Insecticide resistance seriously threatens efficient arthropod pest management. Arthropod glutathione S-transferases (GSTs) confer resistance via direct metabolism or sequestration of chemicals, but also indirectly by providing protection against oxidative stress induced by insecticide exposure. To date, GST activity has been associated with resistance to all main classes of insecticides. However, recent advances in genome and transcriptome sequencing, together with modern genetic, functional and biochemical techniques, facilitate the unraveling of specific GST-mediated resistance mechanisms. Recently, the role of a number of GSTs (BdGSTe2, BdGSTe4, AfGSTe2) has been validated by (reverse) genetic methods in vivo, while a number of GSTs (BmGSTu2, TuGSTd05, AfGSTe2) have now been shown to metabolize insecticides in vitro.